The state of play on international piracy and anti-counterfeiting strategies (Maryland series in contemporary Asian studies, 2012)
I. Introduction : a global pandemic -- II. International strategies and controversies. A. Global Congress Combating Counterfeiting and Piracy (GCCCP) -- B. World Health Organization (WHO)/IMPACT! -- C. International Criminal Policy Organization (ICPO-INTERPOL) -- D. World Customs Organization (WCO) -- E. The Group of Eight (G8) summit -- F. Anti-Counterfeiting Trade Agreement (ACTA) -- G. Asia-Pacific Economic Cooperation (APEC) -- H. Trans-Pacific Partnership Agreement (TPAA) -- III. Outlook and conclusion